Forgery beyond deceit : fabrication, value, and the desire for ancient Rome - Hopkins, John North; Hopkins, John North; McGill, Scott; McGill, Scott (Oxford University Press, 2023)
"What do forgeries do? This book explores that question with a focus on forgery in ancient Rome and of ancient Rome. Its chapters reach from antiquity to the twentieth century and cover literature and art, the two areas that predominate in forgery studies, as well as the forgery of physical books, coins, and religious relics. The book examines the cultural, historical, and rhetorical functions of forgery that extend beyond the desire to deceive and profit. It analyses forgery in connection with related phenomena like pseudepigraphy, fakes, and copies; and it investigates the aesthetic and historical value that forgeries possess when scholarship takes seriously their form, content, and varied uses within and across cultures. Of particular interest is the way that forgeries embody a desire for the ancient and for the recovery of the fragmentary past of ancient Rome"--